2019
DOI: 10.1002/adsu.201900012
|View full text |Cite
|
Sign up to set email alerts
|

A Filter Paper‐Based Nanogenerator via Water‐Drop Flow

Abstract: proposed to harvest the ultrasonic wave's energy using zinc oxide (ZnO) nanowire arrays, [9] the nanogenerator has entered a period of rapid development. [10][11][12][13] Various energies have been harvested using many kinds of nanogenerators, [4] such as triboelectric nanogenerators, [13] PENGs, [14] thermal-electric nanogenerators, [15] and photoelectric nanogenerators. [16] In addition, the as-harvested energy has various resources, such as wind, [17][18][19] heat energy, [20,21] solar power, [22] vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
10
1
Order By: Relevance
“…[26] Instantaneous current peaks higher than 2 mA can be generated by a droplet falling on a charged surface with σ = 0.35 mC m −2 (Figure 2c). This current value is substantially higher than previous reported values, [4,[27][28][29][30][31][32] including the recent DEG approach [9] (Figure 2d; Table S1, Supporting Information). The current response is based on electrostatic induction and can be understood as follows: 1) before a droplet touches the wire, all countercharges induced by the trapped charges are located at the bottom electrode; 2) upon the spreading droplet touches the wire, the countercharges transfer from the bottom electrode to the top electrode, and an electric current signal is generated; 3) after the droplet bouncing off or sliding downhill, the countercharges are again accumulated at the bottom electrode, ready for electricity generation from the next droplet.…”
contrasting
confidence: 60%
See 1 more Smart Citation
“…[26] Instantaneous current peaks higher than 2 mA can be generated by a droplet falling on a charged surface with σ = 0.35 mC m −2 (Figure 2c). This current value is substantially higher than previous reported values, [4,[27][28][29][30][31][32] including the recent DEG approach [9] (Figure 2d; Table S1, Supporting Information). The current response is based on electrostatic induction and can be understood as follows: 1) before a droplet touches the wire, all countercharges induced by the trapped charges are located at the bottom electrode; 2) upon the spreading droplet touches the wire, the countercharges transfer from the bottom electrode to the top electrode, and an electric current signal is generated; 3) after the droplet bouncing off or sliding downhill, the countercharges are again accumulated at the bottom electrode, ready for electricity generation from the next droplet.…”
contrasting
confidence: 60%
“…d) Comparison of the instantaneous peak current value obtained in this work with other reports. [4,[27][28][29][30][31][32] height of 4.3 cm, the maximum spreading area is around 0.7 cm 2 . The maximum transferred charge densities according to Figure 2f are 0.34, 0.19, and 0.07 mC m −2 for these three samples.…”
mentioning
confidence: 99%
“…However, the observed voltage was only microvolts/cm and the fabrication and handling of CNTs is incompatible with large-scale applications. Similarly, it has been observed that a few millivolts can be generated by using carbon black 20 , graphene oxide 27,28 , monolayer graphene 29,30 , as well as carbon-based hybrid systems grown on oxide nanowire networks 31 or cellulose-based lter paper printed with multi-walled CNTs 32,33 . However, most of these carbon-based materials adhere only weakly to substrates, making devices rather fragile and hard to scale up, and the output voltage was below 100 mV/cm 2 range at the largest 22,27,29,30,34,35 .…”
Section: Introductionmentioning
confidence: 97%
“…Regarding height sensors, Xia et al proposed a stacked 3D zigzag-structured P-TENG [ 70 ], which displayed different output signals depending on the changes in height of a falling object or on the impact when this object came into contact with the P-TENG. To increase the overall output, the paper in the zigzag-structured P-TENG was coated with commercial conductive ink.…”
Section: Reviewmentioning
confidence: 99%